IMPROVEMENT OF COMMUNICATIVE SKILLS BY MEANS OF COLLABORATIVE METHODS - Shakhnoza Murakayeva; Lazokat Ikanova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract. Effective communication is an essential skill in both personal and professional contexts. However, developing these skills often requires more than just theoretical knowledge or passive learning. This article explores the role of collaborative methods in enhancing communicative abilities. By focusing on group-based learning, peer interaction, and active engagement, collaborative approaches foster a more dynamic and interactive environment for communication skill development. The effectiveness of methods such as cooperative learning, project-based learning, and peer feedback is discussed, along with their applications in various educational and organizational settings. The article concludes by emphasizing the need for integrating collaborative strategies into communication training programs to better prepare individuals for the demands of contemporary social and professional interaction.